2017
DOI: 10.1039/c7cp05353c
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism of Nystatin action is dependent on the membrane biophysical properties and lipid composition

Abstract: Nystatin (Nys) is a pore forming broad-spectrum and efficient antifungal drug with significant toxicity in mammalian organisms. In order to develop a non-toxic and more effective Nys formulation, its molecular mechanism of action at the cell membrane needs to be better understood. It is widely accepted that Nys activity and toxicity depend on the presence and type of membrane sterols. Taking advantage of multiple biophysical methodologies, we now show that the formation and stabilization of Nys aqueous pores, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…This difference is due to a modification in the distribution of ergosterol rather than in the level of cellular ergosterol, as Ysp2 AAA and WT Ysp2 cells contain the same amount of total ergosterol ( Figure 4B ). The change in PM ergosterol homeostasis was confirmed by showing that cells expressing Ysp2 AAA are more resistant than cells expressing WT Ysp2 to nystatin, another pore-forming polyene antifungal that functions, in part, by interacting with ergosterol in membranes ( Dos Santos et al, 2017 ; Figure 4C ). Therefore, the role of Ypk1 phosphorylation is to negatively regulate Ysp2 function.…”
Section: Resultsmentioning
confidence: 84%
“…This difference is due to a modification in the distribution of ergosterol rather than in the level of cellular ergosterol, as Ysp2 AAA and WT Ysp2 cells contain the same amount of total ergosterol ( Figure 4B ). The change in PM ergosterol homeostasis was confirmed by showing that cells expressing Ysp2 AAA are more resistant than cells expressing WT Ysp2 to nystatin, another pore-forming polyene antifungal that functions, in part, by interacting with ergosterol in membranes ( Dos Santos et al, 2017 ; Figure 4C ). Therefore, the role of Ypk1 phosphorylation is to negatively regulate Ysp2 function.…”
Section: Resultsmentioning
confidence: 84%
“…S13 and S14), suggesting that VdSho1 was not involved in responses to high osmotic stress and cell wall integrity in V. dahliae. Furthermore, VdSho1 sensing of the osmotic stress was determined using the pharmacological agent nystatin, which inhibits the Sho1-mediated signalling and reduce osmotic stress intracellularly by enhancing membrane permeability (Reiser et al, 2003;dos Santos et al, 2017). In the VdSho1 complemented transformants, the growth of ΔSho1 strain was not restricted in response to nystatin ( Fig.…”
Section: Vdsho1 Senses Membrane Permeabilization To Regulate Penetrationmentioning
confidence: 99%
“…The present work shows how the headgroup structure of complex sphingolipids can be an important determinant in the organization of plasma membrane lipids and proteins in S. cerevisiae. Recently, we showed that the polyene antifungal nystatin forms active pores in membranes lacking any sterol, but containing gel domains [12], challenging the classical model which describes the molecular mode of action of nystatin through an ergosterol-dependent mechanism. Moreover, the action of other antifungal drugs has been shown to involve an interplay with sphingolipids that is conditioned by their headgroup structure.…”
Section: Discussionmentioning
confidence: 90%
“…DPH steady-state fluorescence anisotropy, r , is a well-established parameter to report alterations in the global fluidity of the plasma membrane [11,58,59]. The fluorescence anisotropy of DPH changes linearly with composition (and temperature) along the gel/ liquid disordered (l d ) and l d / liquid ordered (l o ) phase coexistence region, i.e., responds linearly to the fraction of each phase, in several binary and ternary lipid systems [12,54,58], including in the 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC)/ergosterol binary system [60]. Moreover, in the POPC/phytoceramide (the yeast sphingolipid backbone) system, the fluorescence anisotropy and intensity of DPH behave similarly to typical gel/ l d systems in the region of coexistence of l d and a phytoceramide-rich gel phase where the hydrophobic packing is comparable to the one found for the gel domains in yeast [48].…”
Section: Membrane Fluidity Is Altered In Ipt1∆ Cellsmentioning
confidence: 99%
See 1 more Smart Citation